Intestinal Obstruction by a Pancreatic Bezoar: A Case Report - Luperto, Margherita; Maternini, Matteo; Ciravegna, Arianna; Degrate, Luca; Lo Bianco, Giulia; Zanella, Stefano; Romano, Fabrizio; Gianotti, Luca (JOP. Journal of the Pancreas, 2014)
<!--[if gte mso 9]> Normal 0 14 MicrosoftInternetExplorer4 <![endif]--> Context Pancreatic pseudocysts are relatively common complications of pancreatitis. A pseudocyst can result from an episode of acute pancreatitis, exacerbation of chronic pancreatitis, or trauma. Treatment is indicated for persistent, symptomatic pseudocysts and in the case of related complications. Case report We describe the case of a 66-year-old man who referred to our department for bowel obstruction caused by a necrotic pancreatic bezoar occurring 16 days after the patient underwent a jejunal-pseudocyst anastomosis performed to treat a post-pancreatitis voluminous pseudocyst obstructing the gastric outlet. Conclusion In case of intestinal obstruction after a jejunal-pseudocyst anastomosis, pancreatic bezoar should be considered in the armamentarium of the differential diagnosis. Image: Bezoar removed through an enterotomy. <!--[if gte mso 10]> <![endif]-->